Gaze-dependent display encryption (2021)
Aspects of the subject technology relate to gaze-dependent visual encryption of electronic device displays. Each display frame that is displayed on the electronic device display may include a clear-display region around the user's gaze location and an obscured region outside the clear-display region. In this way, only the display content that the user is actively viewing is recognizable and understandable and an onlooker such as an unwanted observer looking over the user's shoulder is unable to understand what is displayed. The obscured region of each display frame may be generated such that the overall look and structure of that region is unchanged, but the content is unintelligible. In this way, the visual experience of the user is not disrupted or distracted by the visual encryption and the eye of the onlooker is not guided to the clear-display region by the visual encryption.